Kodifikasi Al-Qur’an: Studi Analisis Sejarah - Inayatullah, Arrijalul Aziz; Safruroh, Safruroh (Lembaga Peneltian Universitas Islam Internasional Darullughah Wadda'wah, 2024)
This research discusses the history of the codification of the Qur'an from the time of Prophet Muhammad (PBUH) to the era of Caliph Uthman bin Affan, which was a crucial process in preserving the authenticity and purity of the Qur'an. The background of this study is based on the importance of understanding the history of the Qur'an's compilation, as this holy book serves as a lifelong guide for Muslims. The purpose of this research is to analyze the stages of the Qur'an's collection and codification, beginning from the Prophet's era, followed by the era of Caliph Abu Bakr, and finalized during the era of Caliph Uthman. The method used in this study is a literature review with a qualitative approach, analyzing various historical sources on the codification process. The results show that the Qur'an was collected through memorization and writing by the companions during the Prophet's time, followed by the compilation of scattered verses into a single mushaf during Abu Bakr's era, and the establishment of an official mushaf during Uthman's era to resolve differences in Qur'anic recitations. The scientific contribution of this research is to provide a comprehensive understanding of the historical process of the Qur'an's codification and how efforts to preserve this holy book have successfully maintained its authenticity to this day.